Elevation and seasonality modulate the leaf decomposition rates and nutrient flux of diverse species and species richness in karst river systems across China - Chen, Zhangting; Arif, Muhammad; Tian, Mengyao (Frontiers in Plant Science, 2025)
Karst river systems (KRSs) are essential to regional biogeochemical cycling and are defined by their distinct geomorphological and hydrological features. Understanding the factors controlling litter decomposition and associated nutrient fluxes within these systems is essential for predicting ecosystem responses to environmental changes. While extensive research is underway on litter decomposition and nutrient dynamics, studies on the interactions between species richness and elevation across seasons in KRSs remain limited. This study investigates the effects of elevation (800 m, 110 m, and 60 m) and seasonality (spring and autumn) on foliage decomposition and associated nutrient fluxes in KRSs along the Li River in China. We examined the foliage decomposition of three species: Taxodium distichum (Linn.) Rich., Taxodium ascendens Brongn., and Salix matsudana Koidz. It included seven litter treatments in single-species and mixed-species litter bags (3 species in all single-, 2- and 3-species combinations). A total of 336 decomposition bags were used to measure leaf mass loss and nutrient release during two six-month periods at three elevations in the study area in 2023. Results revealed that seasonal changes significantly influenced initial leaf elemental concentrations, with spring samples showing the most pronounced effects. Elevation had more effect on mass loss than litter treatments, with distinct nutrient release patterns observed across different elevations. Among single species, S. matsudana exhibited the highest mass loss and nutrient release at lower elevations during spring, while T. ascendens showed the lowest rates in autumn at high elevations. Mixed-species treatments displayed different decomposition patterns, with mass loss and nutrient release following the sequence: T. distichum × T. ascendens × S. matsudana < T. ascendens × S. matsudana < T. distichum × S. matsudana < T. distichum × T. ascendens. Nutrient release in mixed species showed significant interactions with elevation and season, displaying both positive and negative non-additive effects. Correlation analysis indicated stronger relationships between nutrient release and mass loss in S. matsudana than in T. distichum and T. ascendens. This study underscores the intricate interactions between biotic and abiotic factors in KRSs. It highlights the importance of considering elevation and seasonal dynamics in ecological restoration efforts in KRSs.